Design for additive manufacturing - Leary, Martin (Elsevier, 2020)
Design for Additive Manufacturing is a complete guide to design tools for the manufacturing requirements of AM and how they can enable the optimization of process and product parameters for the reduction of manufacturing costs and effort. This timely synopsis of state-of-the-art design tools for AM brings the reader right up-to-date on the latest methods from both academia and industry. Tools for both metallic and polymeric AM technologies are presented and critically reviewed, along with their manufacturing attributes. Commercial applications of AM are also explained with case studies from a range of industries, thus demonstrating best-practice in AM design.
Keywords: Three-dimensional printing.; Manufacturing processes.; elektronické knihy; electronic books